New heinemann maths textbook 3 - Blair, John T; Farren, Percy W (Heinemann Educational London, 2000)
By fostering a positive attitude towards mathematics, the textbook prepares students for more advanced concepts in future terms, ensuring a solid grounding in essential numerical competencies.